NANOSCALE BARIUM HYDROSILICATES: CHOOSING THE SYNTHESIS TECHNOLOGY - GRISHINA Anna Nikolaevna; KOROLEV Evgenij Valerjevich (Нанотехнологии в строительстве, 2013)
Cement concretes are the most used materials in modern civil engineering. Due to that such materials draw great attention both in the Russian Federation and abroad. The possibility to enhance the manufacturability and operational properties of concretes results in significant reduction of overall operating costs. Many enhancement methods have been elaborated. Among them there is one based on introduction of calcium hydrosilicates into construction composition. The authors set up a hypothesis that similarity between properties and structures of different hydrosilicates (for example, alkaline earth metals and metals of the second group) will provide similar increased operational characteristics. The specialists of Research and Educational Center «Nanotechnology» are developing cement composites nanomodification methods which include introduction of nanodimensional barium hydrosilicates particles. The synthesis of barium hydrosilicates particles can be done with the use of many technologies, different by energy consumption or performing complexity. Taking into account both these factors, one can assume that low-temperature sol-gel synthesis from diluted water solutions is the proper technology. The present paper shows that this assumption is correct. The selection of certain technology is made by the means of multiobjective optimization, which is in turn is performed by the means of linear scalarization. This method, while not always giving the Pareto optimal solutions, can be easily implemented. The particle size distribution is taken into consideration during selection of objectives and weights. It is shown that selected technology allows manufacturing nanoparticles with median size about 30 nm.